The Effect of Organizational Culture and Non-Physical Work Environment on Employee Performance at KSP Pintu Air Rotat, Sikka Regency, East Nusa Tenggara - Jagong, Bernadus; Lay, Elly; Nub, Soleman; Gana, Frans (PT Keberlanjutan Strategis Indonesia, 2026)
This empirical investigation was conducted at KSP Pintu Air Rotat, Sikka Regency, to evaluate the individual and collective impact of organisational culture and non-physical work environment on employee performance. By employing a saturated sampling approach, data were gathered from 45 respondents through a combination of structured questionnaires, field observations, in-depth interviews, and archival documentation. Descriptive results, employee organizational culture is categorized as good. the non-physical work environment is very good, and employee performance is very good. effect of organizational culture: organizational culture has a positive and significant partial effect on employee performance. higher levels of organizational culture lead to higher employee performance. effect of non-physical work environment: non-physical work environment has a positive and significant partial effect on employee performance. an improved work environment leads to improved performance. both variables together significantly affect employee performance. the coefficient of determination shows that most variation in performance is explained by these two variables, while the remainder is influenced by other factors such as motivation, discipline, leadership, workload, and compensation.